Assessing the governance mechanisms, corporate social responsibility and performance: The moderating effect of board independence - Karim, Sitara; Abdul Manab, Norlida; Ismail, Rusmawati (Sage Journal, 2020)
This article serves two purposes. First, it attempts to examine the joint impact of corporate governance mechanisms and corporate social responsibility (CSR) practice on firm performance. Second, the moderating role of board independence is investigated on 588 non-financial Malaysian firms listed on Bursa Malaysia during the period 2006–2017. Both accounting-based return on assets (ROA) and market-based (Tobin’s Q) performance measures have been used for measuring performance. Dynamic model using Generalized Method of Moments (GMM) has been employed on the data set to control for potential endogeneity, reverse causality and dynamic heterogeneity. Findings indicate that ROA is a better determinant of firm performance than Tobin’s Q, where ownership concentration, managerial ownership and money spent on CSR negatively affect ROA; however, an insignificant relationship is observed with Tobin’s Q. Finally, board independence negatively moderates governance-CSR and firm performance relationship. Findings of this article have implications for Bursa Malaysia and Securities Commission Malaysia to reset the limit of independent directors on board so that their unnecessary interference in operations of management may be avoided. Furthermore, companies need to reassess their CSR strategies whether they are spending on CSR activities or hiding their financial malfeasance in the name of money spent on CSR.